DAMPAK PENGUNGKAPAN PENDAPATAN KOMPREHENSIF LAIN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Pramestya Galih Bima; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2017)
This study aims to determine the impact of the disclosure of other comprehensive income to earnings management that occurs in a manufacturing company in Indonesia over the period 2014 -. 2015. The variables used in this study is the earning manajement, other comprehensive income, company size, leverage and cash flow from operating activities.This study uses secondary data from financial statements and annual reports published by companies manufacturing in Indonesia. Selection of the samples in this study using purposive sampling method. Data analysis techniques in this study using descriptive statistics and multiple linear regression to determine the impact of the disclosure of other comprehensive income to earnings management. The detection of earnings management using Modfied Jones Models.The results of this study indicate that the disclosure of other comprehensive income tehadap significant influence earnings management practices. The greater the disclosure of other comprehensive income, the greater the restrictions on earnings management practices by managers.